2010
DOI: 10.1677/joe-09-0459
|View full text |Cite
|
Sign up to set email alerts
|

Developmental programming of adult adrenal structure and steroidogenesis: effects of fetal glucocorticoid excess and postnatal dietary omega-3 fatty acids

Abstract: Fetal glucocorticoid excess programs a range of detrimental outcomes in the adult phenotype, at least some of which may be due to altered adult adrenocortical function. In this study, we determined the effects of maternal dexamethasone treatment on offspring adrenal morphology and function, as well as the interactive effects of postnatal dietary omega-3 (n-3) fatty acids. This postnatal dietary intervention has been shown to alleviate many of the programming outcomes in this model, but whether this is via the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 53 publications
4
34
1
Order By: Relevance
“…Waddell et al (2010) found that DEX administered from day 13 to term in pregnant rats did not significantly alter the expression of Star mRNA in the adrenal gland of adult offspring, although plasma and urinary corticosterone and urinary aldosterone were elevated, indicative of enhanced adrenal responsiveness. Low-dose DEX given to rats during late pregnancy has been shown to reduce birth weight and result in hypertension, hyperglycemia, and hyperinsulinemia in adult offspring (Lindsay et al 1996, Holness & Sugden 2001, O'Regan et al 2004.…”
Section: Figurementioning
confidence: 85%
See 1 more Smart Citation
“…Waddell et al (2010) found that DEX administered from day 13 to term in pregnant rats did not significantly alter the expression of Star mRNA in the adrenal gland of adult offspring, although plasma and urinary corticosterone and urinary aldosterone were elevated, indicative of enhanced adrenal responsiveness. Low-dose DEX given to rats during late pregnancy has been shown to reduce birth weight and result in hypertension, hyperglycemia, and hyperinsulinemia in adult offspring (Lindsay et al 1996, Holness & Sugden 2001, O'Regan et al 2004.…”
Section: Figurementioning
confidence: 85%
“…Low-dose DEX given to rats during late pregnancy has been shown to reduce birth weight and result in hypertension, hyperglycemia, and hyperinsulinemia in adult offspring (Lindsay et al 1996, Holness & Sugden 2001, O'Regan et al 2004. Studies in sheep, pigs, and guinea pigs have shown increased HPA axis activity and anxiety-like behaviors in adult offspring (Cadet et al 1986, Lingas & Matthews 2001, Sloboda et al 2002, Jarvis et al 2006, as well as increased adrenal the expression of Mc2r mRNA (Waddell et al 2010), the gene encoding the ACTH receptor (Hirsch et al 2011). These studies strongly suggest that maternal glucocorticoids mediate the effects of maternal stress on the development of the HPA axis in the fetus, and the results of this study in the spiny mouse show that the fetal adrenal gland is particularly vulnerable to high levels glucocorticoids even if they occur only transiently at mid-gestation.…”
Section: Figurementioning
confidence: 99%
“…Our data are in agreement with Waddell et al who reported increased adrenal expression of the ACTH-R in 6-month-old offspring and increased stress-induced levels of plasma corticosterone in a rat model of programming in which dams received dexamthasone during gestation. 18 In humans, low birth weight is associated with increased urinary glucocorticoid excretion in children 57 and with elevated basal plasma cortisol concentration 58 and greater adrenocortical responsiveness to ACTH in adults. 59 This increased responsiveness to stress has been proposed to contribute to the pathogenesis of chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…18 The investigators suggested that the increase in ACTH-R expression in this species may account for exaggerated GC/MC response of these offspring to stress. 18 Maternal undernutrition also alters rat adrenal medullary structure and function, with defective adrenaline secretion in foodrestricted offspring. 19 Since maternal undernutrition is associated with excess maternal GC production which may play a vital role in programming offspring hypertension in the offspring, we sought to characterize maternal as well as offspring adrenal expression of major steroidogenic enzymes involved in glucocorticoid/ mineralocorticoid synthesis along with their respective receptors (see Figure 1) and ACTH-Rs.…”
mentioning
confidence: 99%
“…This apparent contradiction can be explained by the fact that sucrose-treated animals display significantly lower Mc2r expression levels in the adrenal cortex (l'Allemand et al 1996, Lichtenauer et al 2007, Waddell et al 2010. The origin and significance of this finding deserve further investigation.…”
Section: Weeks Of Treatmentmentioning
confidence: 95%